2015
DOI: 10.1007/s00414-015-1226-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of SNP variants affecting hair colour prediction in Europeans

Abstract: DNA profiling is a key tool for forensic analysis; however, current methods identify a suspect either by direct comparison or from DNA database searches. In cases with unidentified suspects, prediction of visible physical traits e.g. pigmentation or hair distribution of the DNA donors can provide important probative information. This study aimed to explore single nucleotide polymorphism (SNP) variants for their effect on hair colour prediction. A discovery panel of 63 SNPs consisting of already established hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 59 publications
0
23
0
8
Order By: Relevance
“…Besides human pigmentation, other visible traits including facial morphology [6], stature [7] and hair shape [8] have all been proposed to provide useful data about an unidentified person. Prediction of externally visible characteristics such as hair colour [9,10] or early onset male pattern baldness [11] are potentially highly informative but are hindered by a lack of accuracy related to changes in phenotypic expression as a person gets older. Therefore, inference of a person's age can provide an important contribution to the following forensic analyses: i. to guide police investigations in the absence of eyewitness testimony or a national DNA database entry; ii.…”
Section: Introductionmentioning
confidence: 99%
“…Besides human pigmentation, other visible traits including facial morphology [6], stature [7] and hair shape [8] have all been proposed to provide useful data about an unidentified person. Prediction of externally visible characteristics such as hair colour [9,10] or early onset male pattern baldness [11] are potentially highly informative but are hindered by a lack of accuracy related to changes in phenotypic expression as a person gets older. Therefore, inference of a person's age can provide an important contribution to the following forensic analyses: i. to guide police investigations in the absence of eyewitness testimony or a national DNA database entry; ii.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the prediction of broad (i.e., categorical) eye and hair colour phenotypes from SNP genotypes is now achievable with practically useful accuracies, for instance by applying the IrisPlex and HIrisPlex DNA test systems that have been forensically validated [31][32][33][34], as well as tested and applied [35,36]. Similar tools for eye and hair colour DNA prediction that largely overlap in SNP predictors with the Iris/HIrisPlex systems have also been generated and used [21,[37][38][39][40][41][42]. This advancement in understanding the genetic basis and DNAbased predictability of eye and hair colour was achievable in part because these two pigmentation traits A C C E P T E D M A N U S C R I P T evolved in genetically homogeneous Europeans that were used in these genetic studies, and therefore are found today almost exclusively in people of (at least partial) European bio-geographic ancestry.…”
mentioning
confidence: 99%
“…Therefore, the predictability of skin colour from DNA [37][38][39] lagged behind that of eye and hair colour [30][31][32][33][34][35][36][37][38][39][40][41][42]. Valenzuela et al [21] obtained a low R 2 value for skin reflectance of 45.7% based on three SNPs.…”
mentioning
confidence: 99%
“…For this, the BioMark™ EP1™ real‐time PCR system (Fluidigm Corp., South San Francisco, CA) was used. Suitable SNPs were selected from various papers about FDP (Pneuman, Budimlija, Caragine, Prinz, & Wurmbach, ; Söchtig et al, ; Walsh et al, ) available through an online search using the National Centre for Biotechnology Information database (NCBI; Table S2). Based on these SNPs custom‐designed SNPtype™ assays were ordered at the Fluidigm® company.…”
Section: Snp Typing With the 19224 Dynamic Arraymentioning
confidence: 99%